RISK IDENTIFICATION AND COST ESTIMATION FOR OCCUPATIONAL SAFETY AND HEALTH (OSH) ON THE GPDI CHURCH CONSTRUCTION PROJECT IN KUTA - Ariany Frederika; A. A. Gde Agung Yana; Putu Audien Marchely (Universitas Udayana, 2025)
Occupational Safety and Health (K3) has been regulated in national regulations and international standards such as OSHA, but BPJS Ketenagakerjaan reported that cases of work accidents increased from 3,174 in 2022 to 5,508 by August 2024. The construction project of the Pentecostal Church Building in Kuta, with an K3 budget of only 0.25% of the project value of IDR 7,444,833,207.00, is below the standard set by the Circular of the Director General of Construction Development in 2018 of 1% to 2.5%. This study aims to identify risks using the Job Safety Analysis (JSA) method and examine the appropriate K3 cost estimates. Primary data is in the form of the number of workers, while secondary data is taken from project documents such as time schedules, planning drawings, Bill Of Quantity (BOQ), and AHSP Badung Regency. Risk analysis is carried out with JSA, identifying work, hazards, and risks using a risk matrix. The K3 cost estimate is calculated from the need for PPE, training, and other K3 facilities, then compared to the total project value. The results of the study showed that 7.27% of risks were identified as very high, 50.91% as high, 40% as medium, and 1.82% as small. The estimated K3 cost required is Rp145,082,002.07 or 1.9% of the project value.